Association of Metabolic Syndrome with Adverse Outcomes in Patients with Stable Coronary Artery Disease: A Meta-Analysis - Su, Yongcai; Zhang, Xiaole (Hormone and Metabolic Research, 2022)
A consensus has not been reached on the association of metabolic syndrome (MetS) with adverse outcomes in patients with stable coronary artery disease (CAD). The purpose of this systematic review and meta-analysis was to summarize the prognostic implication of MetS in patients with stable CAD. We comprehensively searched articles indexing in PubMed and Embase databases until August 14, 2022. Original studies investigating the association of MetS with adverse outcomes in patients with stable CAD were included. Seven studies including 32 736 patients with stable CAD were identified. Depending on the definition of MetS, the reported prevalence of MetS ranged from 23.4% to 63%. Meta-analysis showed that patients with MetS conferred an increased risk of all-cause mortality [risk ratio (RR) 1.22; 95% confidence intervals (CI) 1.15–1.19], cardiovascular mortality (RR 1.49; 95% CI 1.16–1.92), and MACEs defined by death, myocardial infarction, revascularization, cardiac arrest, or angina admission (RR 1.47; 95% CI 1.20–1.79), respectively. Leave-one-out sensitivity analysis indicated the robustness of the value of MetS in prediction of all-cause mortality. MetS may be an independently predictor of adverse outcomes in patients with stable CAD. However, future studies are required to consolidate the current evidence due to the small number of studies included.
Keywords: metabolic syndrome; stable coronary artery disease; cardiovascular mortality; all-cause mortality